Competencies and their Role in Teaching Human Sciences: "The Didactics of History in Tunisia as a model" - Tej, Ramzi Ben Mohamed (Arab Journal for Sciences and Research Publishing, 2020)
The present study seeks to investigate a research topic that has long been contentious for curriculum designers and experts in education and didactics. It presents a concise depiction of the main reasons that lay behind the failure of traditional teaching paradigms. Accordingly, this study highlights the necessary resort to modernization following new international standards that may expunge the drawbacks of former teaching pedagogies. The methodological framework of the present paper is based on rigorous scientific methods: • A historical research method: It seeks the clarification of historical perspectives in relation to education in general and to pedagogy in Tunisia in particular. As such, it depicts a comparison that aims to justify the abandonment of current teaching styles and the adoption of contemporary teaching reforms. • A descriptive approach: It is meant to meet the specificities of the methodological design in order to define the profile of Tunisian educational reality. In this way, the clear chronological pattern opted for in this study helps readers to account for the modifications that have occurred in educational systems. As a result, this study highlights the following major findings: • Competency-based approach has a pivotal role in creating a dynamic atmosphere in teaching and learning, where learners are at the core of the learning process. • The transformation of the interactional classroom pattern from the teacher to the learners, to a more collaborative interactional pattern becomes a necessity. Therefore, this research argues for the necessity to definitively cease rote learning, and above all to accentuate on the profound restructuring of education mainly the establishment of sound foundation for the proper implementation and success of competency – based instruction in the short and long run.